Promoting health equity through the built environment in Duluth, MN: External Resources and Local Evolution Toward Health in All Policies - Katrina Korfmacher (Indiana University-Purdue University Indianapolis, 2020)
Communities, professionals, and researchers recognize that environmental factors contribute to the health inequities experienced by vulnerable populations in the U.S.  These environmental health injustices persist despite well-developed systems for both public health and environmental protection. The root cause of these issues is often "siloed" decision-making by separate health and environmental institutions. Health Impact Assessment (HIA) can be an important tool for bridging these silos to promote health equity at the local level. This raises the question: how can external resources best support local initiatives? This paper examines the interaction between national, state, and non-governmental efforts to promote HIA and local actions to promote healthy and equitable built environment in Duluth, MN. A wide range of local activities in Duluth aimed to alter the long term trends, decision processes, and institutions shaping its built environment. These included integrating health in brownfield redevelopment, local land use plans, food access, and transportation decisions. Technical and financial support from external groups played a key role in developing the community's capacity to promote health equity across public, private, and non-profit organizations. These multiple streams of action culminated in the mayor's declaration in 2016 that health and fairness would be adopted as key goals of the city's new Comprehensive Plan. How did such innovative efforts thrive in a small, post-industrial city with limited resources?  Duluth's experiences provide insight into how external governmental, funding, academic, and non-profit entities can more effectively, efficiently, and equitably support the evolution of local initiatives